The Siete Partidas: A Repository of Mediaeval Military and Tactical Instruction - Jürg Gassmann (Bern Open Publishing, 2021)
The Siete Partidas, compiled in the mid-13th century for the Castilian king Alfonso X el Sabio, constituted the code of law for Castile and later Spain.  Despite the practicality of their instructions and principles on warfare, they are not well studied.  This article will review the military provisions, paying special attention to commanders, the battlefield formations for infantry and cavalry, and the rules on booty and ransom, in the context of the time.  While it is difficult to pinpoint unequivocal influences, the passages are demonstrably practical within the contemporary military doctrine and the ideals of chivalry.  As such, they offer a unique insight into the mechanics of leadership, the battlefield formations of the High Middle Ages, as well as the crucial function of spoils as a source of status-compatible income for the knightly estate and lower nobility, so adding depth and texture to this little-studied yet essential aspect of mediaeval military, economic, and political organisation.